Metformin impairs bile acid homeostasis in ethinylestradiol-induced cholestasis in mice - Faradonbeh, Fatemeh Alaei; Sa, Ivone Igreja; Lastuvkova, Hana; Cermanova, Jolana; Hroch, Milos; Faistova, Hana; Mokry, Jaroslav; Nova, Zuzana; Uher, Martin; Nachtigal, Petr; Pavek, Petr; Micuda, Stanislav (Chemico-biological interactions, 2021)
Metformin, an oral antidiabetic drug, recently demonstrated a reducing effect on bile acids (BA) plasma concentrations in one patient with intrahepatic cholestasis of pregnancy (ICP) by unknown mechanism. Therefore, the aim of the present study was to examine the effect of metformin on BA homeostasis and related molecular pathways in the liver and intestine using a mouse model of ICP. The cholestasis was induced in female C57BL/6 mice by repeated administration of ethinylestradiol (10 mg/kg BW s.c.) and/or metformin (150 mg/kg BW orally) over 5 consecutive days with subsequent bile collection and molecular analysis of samples. We demonstrated that metformin significantly increased the rate of bile secretion in control mice. This increase was BA dependent and was produced both by increased liver BA synthesis via induced cholesterol 7α-hydroxylase (Cyp7a1) and by increased BA reabsorption in the ileum via induction of the apical sodium-dependent BA transporter (Asbt). In contrast, metformin further worsened ethinylestradiol-induced impairment of bile secretion. This reduction was also BA dependent and corresponded with significant downregulation of Bsep, and Ntcp, major excretory and uptake transporters for BA in hepatocytes, respectively. The plasma concentrations of BA were consequently significantly increased in the metformin-treated mice. Altogether, our data indicate positive stimulation of bile secretion by metformin in the intact liver, but this drug also induces serious impairment of BA biliary secretion, with a marked increase in plasma concentrations in estrogen-induced cholestasis. Our results imply that metformin should be used with caution in situations with hormone-dependent cholestasis, such as ICP.
Keywords: hepatocyty; intestinální absorpce; Animals; homeostáza; Female; Intestinal Absorption; metformin; Ethinyl Estradiol; Bile Acids and Salts; ženské pohlaví; Mice; Homeostasis; žlučové kyseliny a soli; Metformin; myši; Hepatocytes; cholestáza; zvířata; Mice, Inbred C57BL; Cholestasis; ethinylestradiol; myši inbrední C57BL